2010
DOI: 10.1627/jpi.53.55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lubricant Additives on Tribochemical Decomposition of Hydrocarbon Oil on Nascent Steel Surfaces

Abstract: A nascent surface has high activity to catalyze the decomposition of lubricants under boundary lubrication conditions. The effects of sulfur-containing, nitrogen-containing, phosphorus-containing additives and phosphatecontaining ionic liquid were investigated on the decomposition of synthetic hydrocarbon oil (multialkylated cyclopentane, MAC). The decomposition processes of the lubricants on the nascent surface of bearing steel AISI 52100 were investigated using a ball-on-disk friction tester in a vacuum cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 19 publications
1
54
0
Order By: Relevance
“…This is in line with previous in-situ measurements that showed emitted hydrogen from tribological contact only happens when sliding occurs on the surface [5,16]. It has also been revealed that lubricant decomposition rate is directly related to sliding velocity and the applied load [13,14,16]. Molecular dynamics simulations [12] have also shown that if a lubricant film is subjected to shearing between two sliding surfaces, both hydrogen diffusion and hydrogen adsorption on the metal surfaces will be induced.…”
Section: The Source Of Hydrogen In a Lubricated Tribocontactsupporting
confidence: 87%
See 4 more Smart Citations
“…This is in line with previous in-situ measurements that showed emitted hydrogen from tribological contact only happens when sliding occurs on the surface [5,16]. It has also been revealed that lubricant decomposition rate is directly related to sliding velocity and the applied load [13,14,16]. Molecular dynamics simulations [12] have also shown that if a lubricant film is subjected to shearing between two sliding surfaces, both hydrogen diffusion and hydrogen adsorption on the metal surfaces will be induced.…”
Section: The Source Of Hydrogen In a Lubricated Tribocontactsupporting
confidence: 87%
“…This will cause serious problems in critical components such as bearings [4][5][6][10][11][12][13][14][15][16]. Uyama et al [6] and Ciruna et al [3] observed that hydrogen content in the AISI 52100 bearing steel is one of the prime reasons for reduced bearing life.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations